The AlkB Family: Potential Prognostic Biomarkers and Therapeutic Targets in Glioblastoma - Feng, Songshan; Xu, Zhijie; Peng, Jinwu; Zhang, Mingyu (Frontiers in Oncology, 2022)
The AlkB family of Fe (II) and α-ketoglutarate-dependent dioxygenases works by removing alkyl substituents from alkylation-damaged nucleic acid bases through oxidative dealkylation, subsequently affecting tumor progression and patient prognosis. However, the specific roles of the AlkB family in Glioblastoma remain to be elucidated. By taking advantage of the abundant bioinformatics databases, such as GEPIA2, cBioPortal and TIMER, we performed a comprehensive analysis of the AlkB family in GBM, and managed to identify the significant prognostic hallmarks and therapeutic targets within this family. We found that the expression levels of ALKBH2 and ALKBH8 were significantly up-regulated in GBM compared with normal tissues. Meanwhile, the patients with high levels of ALKBH2 and ALKBH8 possessed significant poor overall survival (OS). In addition, the results suggested that the biological function of the AlkB family was closely related to DNA damage repair, cell metabolism, cell proliferation and tumor immune infiltration in GBM. Furthermore, the high expression of ALKBH8 in GBM was verified by immunohistochemistry. Taken together, this study could provide meaningful information about the aberrant AlkB family associated with GBM initiation and progression, and help clinicians precisely predict patient survival and select alternative therapeutic drugs.